ANALISIS KESESUAIAN DAN DAYA DUKUNG KAWASAN WISATA PANTAI CERMIN KABUPATEN SERDANG BEDAGAI (Analysis of suitability and carrying capacity of Pantai Cermin area Serdang Bedagai Regency) - Syahru Ramadhan; Pindi Patana; Zulham Apandy Harahap (AQUACOASTMARINE, 2014)
Coastal ecosystems is vulnerable of the environmental changes. Pantai Cermin is the eastern coast of sumatera with foreign and domestic tourist as a well known place since long time. This area is currently in the development and need an analysis of suitability, carrying capacity and zone design to keep sustainability of tourism.The research was conducted in Pantai Cermin area, Serdang Bedagai District, North Sumatera. Tourism activities includes recreation, swim and boating. The aims of this research is to know that this area still in well conditions to held a tourism activities.The result show that in station 1 of recreation area is 81,25 % and station 2 is 85,40 %. Station 1 of swim area is 78,57 % and station 2 is 82,14 % and boating area is 79,17 %. This mean that all the area in well conditions for tourism activity with maximum carrying capacity 260 person/day.Keyword : Ecotourism, suitability tourism, carrying capacity